National Association of Colleges and Employers Job Outlook 2024 (2023)
The Job Outlook survey is a forecast of hiring intentions of employers as they relate to new college graduates. Each year, the National Association of Colleges and Employers (NACE) surveys its employer members about their hiring plans and other employment-related issues to project the market for new college graduates from the current class and to assess a variety of conditions that may influence that market. Data for the Job Outlook 2024 survey were collected from August 2, 2023, through September 18, 2023. Of the 255 total respondents, 180 were NACE employer members, representing 20.3% of eligible member respondents. The Job Outlook 2024 surveywas also distributed to nonmember companies, from which an additional 75 responses were received. Of the total that responded, 7.5% are from New England, 17.6% are from the Mideast, 16.5% are from the Southwest, 8.2% are from the Plains, 12.2% are from the Southeast, 12.5% are from theRocky Mountain/Far West, and 25.5% are from the Great Lakes. For additional information about the respondents, see the Appendix. Data are calculated based on the number of respondents to each specific question. Totals may not equal 100% due to rounding. NACE expects to provide a formal job market update during the 2023-24 academic year. Based on data collected in February and March, the Job Outlook 2024 Spring Update report will give NACE members a final update on hiring for 2023-24 graduates. The report will be available in early April.